2018
DOI: 10.4209/aaqr.2017.04.0126
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Source of Chemical Elements in Size-Resolved Particles in Zhengzhou, China: Effects of Regional Transport

Abstract: To investigate the characteristics of elements in size-segregated atmospheric particulates, samples were collected using a 14-stage electrical low-pressure impactor (ELPI+) at an urban site in Zhengzhou from October 1 till 25, 2016, and analyzed for 25 elements. Results show that crustal elements were concentrated in coarse particles and toxic elements were concentrated in ultra-fine particles. The size distributions of Na, Mg, Al, Si, Ca, Fe, Ti, S and Cl were uni-modal with dominant peaks in the size range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 66 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Ca can be used as a tracer element for dust. Shanghai is located on the east coast of China, and was rarely subjected to long-distance migration of crustal materials from the wind and dust of northwest China and Desert ( Chang et al, 2017 ; Wang et al, 2017 , 2018 ). So, Ca may have originated from road dust or urban construction sites.…”
Section: Resultsmentioning
confidence: 99%
“…Ca can be used as a tracer element for dust. Shanghai is located on the east coast of China, and was rarely subjected to long-distance migration of crustal materials from the wind and dust of northwest China and Desert ( Chang et al, 2017 ; Wang et al, 2017 , 2018 ). So, Ca may have originated from road dust or urban construction sites.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 metallic compounds and elements (Na, Ba, Mg, Sb, Al, Sr, Si, K, Se, Ca, Ti, Ga, V, Ni, Pb, Cu, Zn, As, Fe, Mn, and Cr) in the filters were measured by using an S8 TIGER wavelength dispersive X-ray fluorescence spectrometer (Bruker, Germany), which usage has been approved by the US Environmental Protection Agency (U.S. EPA; Chow and Watson, 1994). Additional information can be found in Wang et al (2018).…”
Section: Chemical Analysismentioning
confidence: 99%
“…reported that southern cities of Henan Province (e.g., Nanyang, Shangqiu, Zhoukou, and Zhumadian) had relatively higher ammonia emissions than the cities involved in this study. Moreover, the northern air masses from the Jing-Jin-Ji regions were easily enriched with sulfate (Wang et al, 2019b;Wang et al, 2018c). The concentrations of chemical composition under stagnant weather conditions in Case 2 clearly increased with average NH4 + , SO4 2− , and NO3 − concentrations that ranged from 12.8 ± 4.5 μg/m 3 (U-ZZ) to 45.5 ± 13.6 μg/m 3 (R-AY ), 30.9 ± 13.4 μg/m 3 (R-XX) to 44.1 ± 17.5 μg/m 3 (R-AY ), and 56.6 ± 19 μg/m 3 (U-AY) to 74.5 ± 20.7 μg/m 3 (R-AY ).…”
Section: Haze Episodesmentioning
confidence: 99%